Research is a Verb: Exploring a New Information Literacy-Embedded Undergraduate Research Methods Course - Polkinghorne, Sarah; Wilton, Shauna (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This presentation introduces a potential solution to widespread and longstanding concerns about undergraduates’ research, writing, and critical thinking skills: a new activity-based, discipline-specific research methods course. The presenters explore course design, course-embedded information literacy learning, course effectiveness evaluation, faculty-librarian collaboration, and the role of reflection in teaching and learning. Cette communication présente une solution potentielle aux préoccupations répandues et de longue date concernant les habiletés de recherche, de rédaction et d'analyse critique des étudiants universitaire de premier cycle : un nouveau cours de méthodologie de recherche basé sur des activités et adaptée à la discipline. La présentation portera sur la conception de cours, des activités pédagogiques favorisant la maîtrise de l'information, l'évaluation de l'efficacité du cours, la collaboration entre professeurs et bibliothécaires et le rôle de la réflexion dans l'enseignement et l'apprentissage. ***Full paper in the Canadian Journal of Information and Library Science***